Do economic policy uncertainty and financial development influence the renewable energy consumption levels in China? - Lei, Wang; Liu, Lihan; Hafeez, Muhammad; Sohail, Sidra (Environmental science and pollution research international, 2022)
Last few decades, several economic uncertainty challenges have emerged in the energy market. This study newly contributes to existing research by inspecting the asymmetric effect of economic policy uncertainty and financial development on renewable energy consumption in China. We employ a nonlinear ARDL approach by using a time-series dataset spanning from 1990 to 2019. Our symmetric model shows that economic policy uncertainty matters in the short run, as it increases renewable energy consumption while exhibiting a negative impact on renewable energy in long run in China. Our asymmetric results in the short and long run have deviated from the symmetric results. Our asymmetric results of the short and long run are similar in direction but different in magnitude. The results show that positive change in economic policy uncertainty has increased 3.216% and negative change in economic policy uncertainty has decreased 1.461% in renewable energy consumption in long run in China. Financial development does not matter in renewable energy consumption in China. Based on these outcomes, we can draw some robust economic policies in China as well as for other pollutant economies. Policymakers should be made economic policies more predictable in the modern era.